Minimal processing of underutilised ingredients for food gel applications - Kremmyda, Alexandra (2024)
Finding an alternative to chemical ways to modify the functional properties of food materials has increased over the last few years. Ball milling has been used recently as a method of physical modification of isolated components (starch, protein) from various botanical sources using mechanical force (centrifugal, impact).